Governing sexuality: the changing politics of citizenship and law reform - Stychin, Carl F. (Bloomsbury collections, 2003)
Introduction -- 1. The Sexual Citizen -- 2. Queering the Third Way: Sexuality and Citizenship in 'New Britain' -- 3. Civil Solidarity or Fragmented Identities: Sexuality and Citizenship in France -- 4. Grant-ing Rights: The Politics of Rights,Sexuality and Citizenship Before the European Court of Justice -- 5. Transnational Citizens: Mobility and Sexuality -- 6. 'We Want to Join Europe, not Sodom': Sexuality and European Union Accession in Romania -- Conclusions.